(untitled) (Journal of Human Sciences, 2021)
The dialect of Fezzan, is one of the Arabic dialects that is taught in language books, due to the importance of this dialect in the Arab heritage , so I thought about writing about it in my research and highlighting itsrelatio-nship to the classical Arabic language with the various phonological and semantic phenomena in it. This research sheds light on one of the dialects of the three regions of Libya, which is the dialect of the Fezzan region and its relationship to cla_ ssical Arabic, by deducing linguistic terms and expressions, in an attempt to draw attention to the fact that the dialect is a feature of the distinct Lib yan identity, and an aspect of national unity in Libya Despite the difficulties that the research faced, including the scarcity of historical and linguistic sources that wrote about this dialect.